Effect of Inorganic and Nano Selenium Supplementation on Growth Performanceand Nutrient Utilization in Growing Hariana Heifers - Aryak Mishra; Raju Kushwaha; Vinod Kumar; Muneendra Kumar; Shalini Vaswani; Avinash Kumar; R.D. Yadav; Mokshata Gupta (Indian Journal of Animal Nutrition, 2025)
The present study was conducted to see the effect of inorganic and nano Se supplementation on growth performance and nutrient utilization in Hariana heifers. In present study, control group was not supplemented with any extra amount of Se other than present in the basal diet, T1 group was supplemented with inorganic Se @ 0.3 mg/kg of DM offered, while T2 group was supplemented with nano Se @ 0.3 mg/kg of DM offered. Basal diet offered to experimental groups containing 50% concentrate, 35% green jowar fodder and 15% wheat straw. DM was offered to all experimental group at about 3.5% of the body weight of animals. All groups of animals were fed with basal diet having same levels of nutrients. Body weight and dry matter intake were recorded fortnightly. DMI (kg/day), DMI (kg/100kg BW), TDN intake (g/kg W0.75) and DCP intake (g/kg W0.75) remained similar in all experimental groups. Nutrient digestibility and digestible nutrient intake were not impacted by supplementation of different levels of inorganic and nano Se supplementation to all treatment groups. Average fortnight body weight gain, ADG, metabolic body weight gain was similar in all groups. FCR and FCE were not significantly different between treatment and control group. So, it can be finally concluded that supplementation of Se either from inorganic or by nano source did not exert any adverse effect on growth performance and nutrient utilization.